2022
DOI: 10.1073/pnas.2122202119
|View full text |Cite
|
Sign up to set email alerts
|

Competition between growth and shear stress drives intermittency in preferential flow paths in porous medium biofilms

Abstract: Bacteria in porous media, such as soils, aquifers, and filters, often form surface-attached communities known as biofilms. Biofilms are affected by fluid flow through the porous medium, for example, for nutrient supply, and they, in turn, affect the flow. A striking example of this interplay is the strong intermittency in flow that can occur when biofilms nearly clog the porous medium. Intermittency manifests itself as the rapid opening and slow closing of individual preferential flow paths (PFPs) through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Furthermore, growth under higher shear stress is known to create more compact and coalescent biofilms, which could also contribute to faster bioclogging as shear rates are higher in the smaller pores for the same Q . Further studies have found that the accumulating mechanical stresses that accompany growth can determine the morphogenesis of clusters, including their internal reorganization or damage as pieces are broken away, and their coalescence. , The interplay between the biofilm cluster growth and the shear stresses is accompanied by the formation of preferential flow paths at later time points . Concluding from our results, the fluid flow, which includes the transported nutrients and the physical forces generated by it, and the geometry of the environment shape the biofilm cluster dynamics by influencing, e.g.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, growth under higher shear stress is known to create more compact and coalescent biofilms, which could also contribute to faster bioclogging as shear rates are higher in the smaller pores for the same Q . Further studies have found that the accumulating mechanical stresses that accompany growth can determine the morphogenesis of clusters, including their internal reorganization or damage as pieces are broken away, and their coalescence. , The interplay between the biofilm cluster growth and the shear stresses is accompanied by the formation of preferential flow paths at later time points . Concluding from our results, the fluid flow, which includes the transported nutrients and the physical forces generated by it, and the geometry of the environment shape the biofilm cluster dynamics by influencing, e.g.…”
Section: Resultssupporting
confidence: 54%
“…58,59 The interplay between the biofilm cluster growth and the shear stresses is accompanied by the formation of preferential flow paths at later time points. 60 Concluding from our results, the fluid flow, which includes the transported nutrients and the physical forces generated by it, and the geometry of the environment shape the biofilm cluster dynamics by influencing, e.g., the mean cluster area as well as the cluster number.…”
Section: Biofilm Cluster Dynamics 311 Temporal Dynamics Of Cluster Nu...mentioning
confidence: 63%
“…In addition, biofilm development within porous media has been demonstrated to be enhanced with high flow rates, as it corresponds to higher shear. 16…”
Section: Numerical Modeling 231 Fluid Flow and Transportmentioning
confidence: 99%
“…The growth of biofilms in porous media alters the pore structure drastically. , This impacts hydrodynamics by creating preferential paths that cause flow channeling , and intermittency when the system approaches full clogging (i.e., the opening and closing of individual preferential flow paths and their spatial rearrangement). , Biofilms have been demonstrated to have spatially and temporally varying physical (e.g., porosity , ), rheological (e.g., shear strength), and hydraulic (e.g., permeability) properties. However, there is a significant challenge while trying to measure biofilm properties, and permeability in particular, due to the inability of most techniques to characterize biofilm structure without significantly affecting its properties .…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of current studies have focused on steady ow, i.e., time-invariant constant ow, despite the fact that uctuating ows are common in a wide variety of natural and industrial environments, such as in rivers due to rainfalls and droughts [22][23] , in pipes due to intermittent water usage [24][25] , and in circulatory systems due to pulsating heartbeat [26][27] . Fluctuating ow can impact bio lm development because the oscillatory components of uctuating ows alter the real-time distribution of pressure, velocity, and shear stress, as well as mixing and nutrient transport rates [28][29] . While we expect ow uctuations can impact bio lm development, it remains unclear how they impact bio lm thickness and morphological structures.…”
Section: Introductionmentioning
confidence: 99%